Supershear cascading rupture envelopes: a case study from the 2023 Kahramanmaraş seismic doublet - Zaccagnino, Davide; Stabile, Tony Alfredo; Akinci, Aybige; Herrero, André; Tan, Onur; Telesca, Luciano; Doglioni, Carlo (Frontiers in Earth Science, 2025)
Super-shear ruptures, characterized by velocities exceeding the shear wave speed, were first predicted theoretically and later observed in laboratory experiments. While a few tectonic earthquakes have been reported as super-shear, most involve strike-slip faults, including the 2023 Mw 7.5 Kahramanmaraş earthquake (Türkiye) and transient phases of the Mw 7.8 event. However, natural ruptures propagate through complex, rough fault systems - deviating from idealized smooth interfaces - resulting in heterogeneous slip, stress drops, and rupture jumps. Additionally, the expected high-frequency spectral signature of super-shear ruptures often conflicts with observations. To reconcile these discrepancies, we propose a generalized interpretation of super-shear events, where observed super-shear velocities arise not only from continuous rupture fronts but also from dynamically triggered multi-focal ruptures along strike. We explore how fault rheology modulates rupture speed and introduce a triggering mechanism driven by P-wave perturbations. Our model also predicts Mach cones detected teleseismically during super-shear earthquakes such as the Kahramanmaraş doublet, while it suggests they should not be observed locally in the case of super-shear cascading rupture envelopes. We show that both the Kahramanmaraş 2023 events initiated cascading instabilities, with dynamic stress transfers propagating rupture across fault patches. High-frequency (>10 Hz) P-wave pulses mark transitions between patches, identified via accelerometric waveform analysis. Our findings support the idea that even minor stress perturbations can trigger near-instantaneous dynamic ruptures, posing implications for early-warning algorithms.